DICOMFlow Access: controle de acesso para compartilhamento de imagens médicas em ambiente aberto e distribuído - Silva, Denys Alexandre Barboza da (2019)
The need for associations between entities from the most diverse areas for information sharing becomes increasingly common. Thus also it happens with the teleradiology, a telemedicine component that uses information technology to issue remote diagnostics through the sharing of medical images. However, the infrastructure (PACS / DICOM) in radiology departments is well consolidated in a local network environment, requiring adaptations to act in a global communication context that uses the Internet as an interconnection infrastructure between entities. One of these adaptations is the performance of access control to information shared between associated entities. Limitations were observed in current access control proposals to manage the authentication and authorization of shared information in a globallyopen and distributed network, limiting themto operate in a networkwiththesecharacteristics. The objective of this work was to elaborate the DICOMFlowAccess, an access control model for na open and distributed collaborative network for the practice of teleradiology. Forthispurpose, theDigitalCertiﬁcateofAttributesspeciﬁedbyICP-Brazilandother technologies already consolidated in the Internet was used, as digital certiﬁcate of identity, email infrastructure and content transmission protocols. Experiments in a virtual environment simulating a collaborative network between distinct entities, attest to its technical and operational feasibility. It was concluded that DICOMFlowAccess was successful in providing access control to shared medical image exams in an open and distributed collaborative networkin a global context of communication formed by distinct entities that use the Internet as a means of interconnection.